Cryptocurrency and Crypto Assets in the Perspective of Islamic Legal System Philosophy - Abadi, Khafid; Ahmad Taufiq; Rizka Roikhana (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
The purpose of this research is to determine whether or not cryptocurrencies are legitimate in Islam as both a currency and a commodity. This is research done in a library. The research is descriptive-analytical and uses Jasser Auda's Islamic legal philosophy approach to try to explain cryptocurrency law. The findings demonstrate that, from the standpoint of Islamic legal philosophy, the law governing cryptocurrency as a currency is comprehensive (tafsil). Whether it is halal or not by looking at how the goal was achieved, specifically (benefit). If the cryptocurrency has clear benefits, such as the existence of underlying assets and the government's role in realizing the general benefit (maslahah ammah), it can be considered halal. Similarly, cryptocurrencies that lack clear regulations and are not backed by assets will be haram due to the possibility of mafsadat. Despite the fact that cryptocurrencies are regarded as al-Ma'l al-ma'nawiyyah because they do not conform to the objectives of sharia in assets (maqashid as-shari'ah fi al- mal), the law of cryptocurrencies as assets (crypto assets) is not valid. This research certainly has limitations, especially related to field data, namely interviews with cryptocurrency business actors. Therefore, to develop further research, not only juridical research but also juridical-empirical research.